PEDAGOGIC FUNCTIONS OF TEACHERS’ CODE-SWITCHING IN GARUDA BILINGUAL KINDERGARTEN - I Gusti Ayu Arya Satyani Pinatih (Universitas Pendidikan Ganesha, 2019)
Even though codeswitching has become a natural phenomenon and occurred in regular basis during the teaching and learning process in bilingual classroom, the pedagogic analysis of the occurring switches should be taken into account to figure out whether the switches are indeed a pedagogic tool used by bilingual teachers for the comprehension and achievement of the lesson content. Therefore, the objective of this study is to figure out the functions of teachers’ code‐switching during classroom teaching and learning process in Garuda Bilingual Kindergarten. This study was conducted using a descriptive qualitative design. The data were collected through classroom observation and recordings. The obtained data were analyzed based on the coding categories of pedagogic function theory. The findings indicate that the functions of the occurring code‐switching are: 1) instructional for content acquisition, 2) reformulation of content, 3) facilitation, and 4) habitual. The result of this study is expected to be useful especially for teachers to know the role of code‐switching in supporting the emergent bilinguals during classroom teaching and learning process as well as to help teachers plan a more effective language strategy.